Implementation of an Integrated Guided Inquiry Learning Model in Generic Science Skills to Improve HOTS - Chiasrilya Maria Hutabarat; Marudut Sinaga (Universitas Negeri Medan, 2024)
This research aims to determine the effect of evaluation of prior knowledge and student worksheets on students' high order thinking skill (HOTS) expressed in the form of learning outcome evaluation using an integrated guided inquiry learning model of generic science skills. The research design used is a dual paradigm with two independent variables, namely evaluation of prior knowledge with student worksheets, and one dependent variable, namely learning outcome evaluation. This research was carried out at SMA Negeri 14 Medan in the 2022/2023 academic year with the research population being all students in class XI Science and the sample in the research was class XI Science 3 which was obtained through a purposive sampling technique. The instruments used in this research consisted of the evaluation of prior knowledge with learning outcome evaluation each have 30 questions and the student worksheets has 15 questions. The research results show that there is a significant influence between evaluation of prior knowledge and student worksheets on students' higher-order thinking skill. Apart from that, there are also differences in higher order thinking skill between students with low evaluation of prior knowledge and students with high evaluation of prior knowledge.